New probabilistic methods for quantitative climate reconstructions applied to palynological data from Lake Kinneret - T. Netzel; A. Miebach; T. Litt; A. Hense (Climate of the Past)
Quantitative local paleoclimate reconstructions are an important tool for gaining insights into the climate history of the Earth. The complex age–sediment–depth and proxy–climate relationships must be described in an appropriate way. Bayesian hierarchical models are a promising method for describing such structures.